More than a She-recession: Long-term feminization and short-term pandemic effects - Linnea Nelli; Maria Enrica Virgillito (Global Labor Organization (GLO), 2023)
The Covid-19 crisis has been defined as a "She-recession" because of its disproportionate impact on female employment by contrast to past recessions defined as "Man-recessions", for the usual disproportionate impact on men. The roots of the She-recession can be however traced back to the persistence of gender asymmetries both intra-household and extra-household in the labour market, a phenomenon known as feminization. This paper aims at measuring and explaining the gender differences in the impact of the Covid-19 crisis on the Italian labour market from a macroeconomic perspective. We measure the duration, depth and diffusion of the Covid-19 crisis on job losses, structural unemployment and inactivity. We find that the impact of the Covid-19 crisis has been more than proportional for women, especially for low educated female workers and working in the South during 2020.
Keywords: J16; E32; J6; 330; feminization; hysteresis; labour markets